Thermodynamic performance study on the novel efficient flow pattern global construction evaporator - Tianming Zhong; Haoxian Bai; Shu Chen; Junrong Yang; Zhilin He; Lixing Ding; Haokun Li (Case Studies in Thermal Engineering, 2024)
Based on the fluid-efficient flow pattern global construction heat transfer enhancement mechanism, a novel evaporator, called the efficient flow pattern global construction evaporator (EFGE), is presented to improve the in-tube evaporation heat transfer at low quality. The numerical analysis and experimental study of EFGE's thermodynamic performance are performed. Results show that the temperature distribution characteristic of the fluid-efficient heat transfer flow pattern construction is better than that of the initial fluid. The evaporation heat transfer coefficient (HTC) of EFGE is 0.34–1.04 times that of a common parallel flow evaporator (PFE), and the pressure drop of EFGE is only 80%–116 % of that of a common PFE at the quality of 0.9. The theoretical nonuniformity of the evaporation HTC between low- and high-quality flow is approximately 12%–67 %, which is 55%–72 % of the pressure drop. The numerical analysis results agree with the finding that EFGE has better thermodynamic performance than PFE in terms of friction power reduction and minimum entropy generation number.